Pronunciation Error Analysis of Halq Phonemes: Case Study in Mawa’idzunnisyan Islamic Boarding School - Subhi, Muhamad; Mursidin, Mursidin (Abjadia : International Journal of Education, 2026)
Arabic possesses a high degree of phonological complexity due to the existence of distinctive phonemes, which poses a major challenge for non-native learners, especially those whose first language (L1), such as Indonesian, lacks these sounds. The imprecise realization of phonemes directly affects semantic comprehension and communication effectiveness. This study employed a qualitative error analysis approach based on diagnostic data from 21 student at Mawa’idzunnisyan Islaming Boarding School to identify, classify, and clarify the phonological deviations. The research focuses on three aspects: identifying the Arabic phonemes most vulnerable to error and determining their error frequency; describing the resulting error typology and analyzing the role of L1 phonological interference in explaining the observed error patterns. The research findings indicate that the Ḥalq phonemes ع, ح, خ are critical phonemes with the highest error rates (reaching 61,9% of cases), predominantly showing the substitution typology. The most frequent substitutions involve the replacement of ح with ه and ع withأ . These error patterns are strongly explained by L1 interference, where learners attempt to replace target phonemes with the closest sounds present in the Indonesian phonological system. This study strives to identify critical phonemes, describe dominant error patterns, and outline the root causes of errors through an examination of L1 interference. These results provide an empirical foundation for adjusting instructional materials, particularly through contrastive articulatory drills targeting pharyngeal and uvular fricatives absent in Indonesian.